Design of an environmental interpretation proposal as an educational resource in a nature reserve in Tandil, Buenos Aires, Argentina (Biocenosis, 2023)
The current context of distancing society from nature has caused environmental problems that need to be minimized. For this reason, it is essential to generate actions that contribute to reconnect social groups with the environment. In this sense, environmental education appears to be the appropriate strategy to carry out this task. This can be implemented through differentinstruments such as environmental or heritage interpretation, protected areas being favorable places to restore these links, thus allowing the generation of environmental awareness and a critical and reflective attitude about human actions. Taking into account the above, the general objective is to promote actions from the interpretation of heritage, which allow the revaluation of the Sierra del Tigre Natural Reserve (Tandil, Argentina) to contribute to the creation of environmental awareness, critical thinking and commitment to sustainability at the individual and collective level. This work is part of an extension project aimed at establishing processes of knowledge and experience exchange between university actors corresponding to the Faculty of Human Sciences of the Universidad Nacional del Centro de la Provincia de Buenos Aires and the members of the cooperative of the Sierra del Tigre Natural Reserve located in the city of Tandil.
Keywords: protected areas; conservation; natural heritage; cultural heritage; environmental education